A snapshot survey of perceptions of healthcare professionals on ageing surgeons. Issue 1097 (4th July 2016) - Rajaratnam, Vaikunthan; Kumar, Chandra M; Roy Chowdhury, Anupama; Su, Chang
ABSTRACT: Objective: The aim of this research was to understand healthcare professionals' perception of the continued practice of ageing surgeons in Singapore. Methodology: A quantitative method was chosen for this research to determine healthcare professionals' perception of the practice of ageing surgeons. Ethical approval was obtained from the local ethical review board. A cross-sectional method using a population survey was performed among healthcare professionals in two tertiary institutions and the study was confined to stakeholders in practices of ageing surgeons. The population sampled was limited to nurses in the theatre, anaesthetists, surgeons and geriatricians (physicians). An online questionnaire was designed for the survey that took into consideration the various conceptual frameworks of ageing surgeons' practice that was obtained from a literature review. Results: There were 104 respondents of a population of 350 sampled (theatre nurses, anaesthetists, physicians and surgeons) giving a respondent rate of 30%. The mean age of the participants was 39.7; 72% were doctors (surgeons 34%, physicians 20% and anaesthetists 18%) and 28% nurses. Only 35% agreed with the statement that older surgeons face deterioration in cognitive faculties and 29% remained neutral. A similar trend was seen with the perception that older surgeons face a decline in memory. However, 44% agreed with the statement that older surgeons face a decline in visuospatial ability and another 40% agreed that they had a decline in psychomotor skills and reaction time. Fifty per cent agreed with the statement that they face deterioration in physical abilities. Sixty-three per cent did not think that older surgeons face a decline in reasoning and judgement. Forty-eight per cent believed that older surgeons' vast fund of knowledge and experience could compensate for physical and cognitive changes. Only 13% agreed with the statement that older surgeons have higher surgical mortality. Forty-five per cent agreed that the retirement age should be 65 while 22% believed it should be over 65. Forty-four per cent agreed that a regular multidisciplinary, objective and comprehensive evaluation of an older surgeon's physical and cognitive function would help to identify and treat reversible problems which when corrected would aid in restoring the surgeon's function. Seventy-four per cent felt that it was the responsibility of all stakeholders to decide or report on when an ageing surgeon is unsafe to continue practicing. Fifty-five per cent disagreed with a mandatory retirement age for surgeons. Conclusions: This study showed that, in Singapore, stakeholders agreed there are changes in physical and cognitive abilities of ageing surgeons but they thought that these can be overcome with selective strategies to optimise their role in the workforce. They also disagreed on a mandatory retirement age.